1999
DOI: 10.1021/ma981773z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Poly(cyanoacetylene) Using Late-Transition-Metal Catalysts

Abstract: Poly(cyanoacetylene) has been prepared by polymerization of cyanoacetylene using a variety of late-transition-metal (Pd- and Ni-based) catalysts. The effect of reaction conditions on molecular weight and polymer yield was explored. Significant catalyst residues remain in the polymer samples. However, spectra are consistent with the proposed poly(cyanoacetylene) structure. Notable differences in molecular weight, effective conjugation length, and ability to undergo thermal cyclization to a supposed aromatic lad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 100 publications
1
16
0
Order By: Relevance
“…Of particular interest was if the nonfluorinated or the partially fluorinated blend membranes show better VRFB performance, since the electrolytes which are present in VRFB are strongly oxidizing, and keeping in mind that the binding energy of C-F bonds is higher than that of C-H bonds 20 . In an earlier study, in which the radical stability of different base-excess base-acid blend membranes including S1B1 and S2B2 blend membranes in Fenton´s reagent was investigated, it could be shown that the partially fluorinated S1B1 blend membrane lost less weight than the nonfluorinated S2B2 blend membrane, indicating a better radical stability of the partially fluorinated blend 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest was if the nonfluorinated or the partially fluorinated blend membranes show better VRFB performance, since the electrolytes which are present in VRFB are strongly oxidizing, and keeping in mind that the binding energy of C-F bonds is higher than that of C-H bonds 20 . In an earlier study, in which the radical stability of different base-excess base-acid blend membranes including S1B1 and S2B2 blend membranes in Fenton´s reagent was investigated, it could be shown that the partially fluorinated S1B1 blend membrane lost less weight than the nonfluorinated S2B2 blend membrane, indicating a better radical stability of the partially fluorinated blend 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated polymers containing mesogenic and chromophoric units can potentially show very high carrier mobility and emit polarized light and may find unique applications and stimulate technological innovations in the development of novel electronic and photonic devices such as light-emitting diodes, photovoltaic cells, thin-film transistors, and plastic lasers. , Realization of these captivating potentials requires the development of versatile processes for the syntheses of such polymers. Polyacetylene is an archetypal conjugated macromolecule and its functionalization has attracted much synthetic effort over the past decades. A variety of polyacetylenes containing liquid-crystalline mesogens and light-emitting chromophores have been prepared, almost all of which are, however, monosubstituted from a structural viewpoint. These monosubstituted polyacetylenes show multifaceted mesophases, with their transition temperatures tunable by their molecular structures. 5a,, The mesogenic orientations of the polymers and their molecular arrangements can be readily manipulated by such external stimuli as mechanical forces 13 and electrical field …”
Section: Introductionmentioning
confidence: 99%
“…Some complexes of nickel are included in this category. Thus, [Ni(PPh 3 ) 4 ] 16 and [Ni(PPh 3 ) 2 Cl 2 ] 17 have been tested in several conditions as catalysts for the polymerization of cyanoacetylene, affording poly(cyanoacetylene) in low to moderate yields (15 to 73 %) and high molecular weight (61.5 10 3 D in the best case), [39] but the final structure of the polymers was not reported. The Ni (COD)-CF 3 COO(allyl) (18) system has been used in the polymerization of phenylacetylene and substituted phenylacetylenes, with moderate to good yields (41 to 65 %) and molecular weight (in the order of 10 4 D), but the reaction is not stereoselective [40].…”
Section: Catalysts That Operate Via Insertion Mechanismmentioning
confidence: 99%